A case study of liquefaction: demonstrating the application of an advanced model and understanding the pitfalls of the simplified procedure. Issue 6 (22nd May 2019) - Tsaparli, Vasiliki (vasia); Kontoe, Stavroula; Taborda, David M. G.; Potts, David M.
Abstract : The complexity of advanced constitutive models often dictates that their capabilities are only demonstrated in the context of model testing under controlled conditions. In the case of earthquake engineering and liquefaction in particular, this restriction is magnified by the difficulties in measuring field behaviour under seismic loading. In this paper, the well-documented case of the Canterbury earthquake sequence in New Zealand, for which extensive field and laboratory data are available, is utilised to demonstrate the accuracy of a bounding surface plasticity model in fully coupled finite-element analyses. A strong motion station with manifestation of liquefaction and the second highest peak vertical ground acceleration during the 22 February 2011 M w 6·2 seismic event is modelled. An empirical assessment predicted no liquefaction for this station, making this an interesting case for rigorous numerical modelling. The calibration of the model aims at capturing both the laboratory tests and the field measurements in a consistent manner. The characterisation of the ground conditions is presented, while, to specify the bedrock motion, the records of two stations without liquefaction are de-convolved and scaled to account for wave attenuation with distance. The numerical predictions are compared to both the horizontal and vertical acceleration records and other field observations, showing a remarkable agreement, also demonstrating that the high vertical accelerations can be attributed to compressional resonance. The results provide further insights into the underperformance of the simplified procedure.